Influence of a Polyimide Coating Layer on Losses of Fabricated SOI Slot Waveguides - Salih, Maithem Naeem; Mickelson, Alan (Photonics Letters of Poland, 2023)
We demonstrate experimentally and simultaneously the impact of the Polyimide (PI) coating layer on the coupling and propagation losses of the fabricated SOI slot waveguides at 1550 nm operation wavelength and TE polarization. Full Text: PDF References P. Dong, Y.K. Chen, G.H. Duan, and D.T. Neilson, "Silicon photonic devices and integrated circuits," Nanophot, 3, 215 (2014). CrossRef Q. Xu, V.R. Almeida, R.R. Panepucci, M. Lipson, "Experimental demonstration of guiding and confining light in nanometer-size low-refractive-index material," Opt. Lett., 29, 1626 (2004). CrossRef V.R. Almeida, Q. Xu, C.A. Barrios, M. Lipson, "Guiding and confining light in void nanostructure," Opt. Lett., 29, 1209 (2004). CrossRef A. Mickelson, "Silicon photonic slot guides for nonlinear optics," 2013 Int. Conf. Microw. Photonics, ICMAP 2013, (2013). CrossRef A. Martínez et al., "Ultrafast all-optical switching in a silicon-nanocrystal-based silicon slot waveguide at telecom wavelengths," Nano Lett., 10, 1506 (2010). CrossRef C. Koos et al., "All-optical high-speed signal processing with silicon-organic hybrid slot waveguides," Nat. Photonics., 3, 216 (2009). CrossRef Y. Li, K. Cui, X. Feng, Y. Huang, F. Liu, and W. Zhang, "Ultralow propagation loss slot-waveguide in high absorption active material," IEEE Photonics J., 6, 3 (2014). CrossRef Z. Wang, N. Zhu, Y. Tang, L. Wosinski, D. Dai, S. He, "Ultracompact low-loss coupler between strip and slot waveguides," Opt. Lett., 34, 1498 (2009). CrossRef